In-vitro biological screening of methanol extract of syzygium tetragonum (Myrtaceae) leaves - Yeasmin, Sadia (Brac University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.